The processes of engagement in information-seeking behavior for individuals with diabetes who developed diabetic foot ulcer: A constructivist grounded theory study - Idevania G Costa; Pilar Camargo-Plazas (Digital Health, 2023)
To describe the process of engagement in information seeking behavior for individuals with type 1 and type 2 diabetes. Methodology Constructivist grounded theory. The data was gathered through thirty semi-structured interviews of participants attending a wound care clinic in Southeast, Ontario, Canada. The waiting period taken to seek appropriate help varied from weeks to months. Results “The processes of engagement in information-seeking behavior about diabetes” are organized as follows: 1) discovering diabetes, 2) reactions to the diagnosis, and 3) engaging in self-directed learning. For most participants, the diagnosis of diabetes was unexpected and usually confirmed after a long period of experiencing a diversity of symptoms. The terms used mostly by participants were “I started to wonder” and “Something was wrong with me.” After being diagnosed with diabetes, participants sought information to learn about it. Most of them engaged in self-directed learning to acquire knowledge about their illness. Conclusion Although the Internet is often used to seek information, healthcare providers and support network also played an important role in supporting participants information-seeking behavior learn about diabetes. The unique needs of people with diabetes must be taken into consideration during their diabetes care journey. These findings call for the need to provide education about diabetes from the time they are diagnosed and direct them to reliable resources of information.